Greenhouse Gas Emission Estimation and Sustainable Municipal Solid Waste Management Development Strategy in Banda Aceh - Anggraini, Wahyu Utami; Fathma, Syarifah Seicha; Harahap, Juliansyah (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
omestic waste management activities produce greenhouse gases (GHG) that account for 3-4% of the world's total GHG sources. Waste processing such as the decomposition process in landfill activities,  Aerobic and anaerobic processes in organic waste composting, and open burning waste also contributes to GHG emissions in the form of CO2, CH4, N2O, and other gases. This study aims to integrate the IPCC 2006 (Tier 2) greenhouse gas inventory method with the Sustainable Balanced Scorecard (SBSC) technique to bridge the gap between emissions quantification and strategic environmental planning. This aims to support greenhouse gas emission reduction in the municipal solid waste management sector. The IPCC 2006 methodology was conducted to calculate greenhouse gas emissions, while the SBSC was utilized for transforming the emission assessment results into strategic environmental recommendations for emission reduction. This research uses secondary data obtained from DLHK3 Banda Aceh City and primary data in the form of the results of filling out questionnaires on 5 selected informants. GHG emissions of Banda Aceh City in the 2050 BaU scenario reached 11,752 Gg CO2-eq, with landfilling producing the largest GHG of 10,755 Gg CO2-eq. Meanwhile, if it is assumed that waste management conditions are in accordance with Scenario 2, the total GHG emissions in domestic waste management in 2050 will be 6,935 Gg CO2-eq. Based on the SBSC analysis, recommendations are arranged based on the lowest performance values, namely, in the environmental perspective and the social perspective.